Biomarkers for central serous chorioretinopathy - Nkrumah, Gideon (Ther Adv Ophthalmol, 2020)
Central serous chorioretinopathy (CSCR) is a common chorioretinal disease characterized by serous retinal detachment that most commonly involves the macular region. Although the natural history of the acute form shows a self-limiting course, a significant number of patients suffer from recurrent episodes leading to chronic disease, often leaving patients with residual visual impairment. Visual morbidity is often worsened by a delay in the diagnosis due to the incorrect understanding of the particular biomarkers of the disease. The aim of this review is to provide clinical understanding of the biomarkers of CSCR with an emphasis on the most recent findings in patient demographics, risk factors, clinical imaging findings, and management options. Patients with these biomarkers, age 30–44 years, male gender, increased stress levels, hypercortisolism (endogenous and exogenous exposures), sleep disturbance, pregnancy, and genetic predisposition have increased susceptibility to CSCR. Also, biomarkers on optical coherence tomography (OCT) such as choroidal thickness (CT) and choroidal vascularity index (CVI) showed good diagnostic and prognostic significance in the management of CSCR. There are nonspecific features of CSCR on OCT and OCT angiography such as choroidal neovascularization, photoreceptor alteration/cone density loss, and flat irregular pigment epithelium detachment. We described rare complications of CSCR such as cystoid macular edema (CME) and cystoid macular degeneration (CMD). Patients with CME recovered some vision when treated with anti-vascular endothelial growth factors (anti-VEGFs). Patients with CMD had irreversible macular damage even after treatment with anti-VEGFs.